(untitled) (Altre Modernità, 2012)
In the work of the Chilean narrator Maria Luisa Bombal, the representation of the garden mentions the biblical paradise. Nevertheless, this dialogue with the tradition presents/displays some variations that repel in the constructed feminine subjectivities in this ethos paradisiac that we have defined as landscape. Thanks to certain rhetorical figures like the elipsis and to the suspension of the perspective in the landscaping composition, the feminine personages of Maria Luisa Bombal merge in the nature and rather happen telluric forces that are identified not like subjects founded on Metaphysical values, but like ghostly voices. The entailment of the subject, understood like an historical construction, with the paradisiac space that lives or longs for is given by the notion of landscape, resource that allows to establish interdisciplinary bridges between the narrative of the Chilean author and the plastic one.